Pengolahan Limbah Cair Industri Elektroplating dengan Proses Flotasi Menggunakan Methyl Ester Sulfonate (MES) sebagai Collector - Laurentius Urip Widodo; Sholekhah, Bika Amalia; Hubbi Hikmatu Ilma (Journal of Research and Technology, 2021)
Industrial waste is a major problem for countries that are developing large industries such as Indonesia. Industrial waste with heavy metal content such as electroplating waste cannot be disposed of directly into the water because it can cause environmental pollution. Therefore, further processing is needed to reduce or eliminate metal levels in the waste water. In this study, the method used to reduce Cu metal content in electroplating waste is using the flotation method. Flotation is the process of separating minerals or ions through flotation with the help of air bubbles to the surface of the water. The parameters observed in this study were the effect of pH and collector on % Cu removal. Experiments were carried out with waste water feed containing Cu metal with an initial concentration of 107.6 mg/L, with a variation of pH 4,5,6,7,8 and a variation of the concentration of 200 mg/L, 300 mg/L, 400 mg/L, 500 mg/L and 600 mg/L of collector. After being analysed using Atomic Absorption Spectrophotometer (AAS), the best% Cu removal at pH 6 conditions and 300 mg/L methyl ester sulfonate (MES) concentration was 67.19%.